Mortality of inpatients due to diabetic foot in a hospital in Costa Rica (2017-2019) - Rojas-Bonilla, José María; Camacho-Álvarez, Yeimi; Campos-Zamora, Kattia; Román-González, Tania; Alvarado-Prado, Rebeca; Romero-Zúñiga, Juan José (Horizonte Sanitario, 2023)
Objective: To identify clinical and sociodemographic factors associated with mortality in patients hospitalized for diabetic foot, in the Diabetic Foot Unit of the San Juan de Dios Hospital in Costa Rica, from 2017 to 2019. Materials and methods: A retrospective cohort study with 238 patients, followed from hospitalization until death or until December 31, 2021, still alive. A descriptive analysis is made of the sociodemographic, clinical, and cause of death variables. A Cox proportional hazards model is run for all causes of death, and another exclusively for death from cardiovascular causes. Survival times are analyzed using Kaplan-Meier curves, with the log-rank test for comparison. Results: Most of the deceased were men, did not have a partner, lived in urban or predominantly urban areas, were 15 years or older, diabetic, hypertensive, with peripheral arterial disease, anemia, inadequate glycosylated hemoglobin, and obesity. The mortality rate was 23,53%, and cardiovascular disease was the main cause of death (35,70%). The variables associated with all-cause mortality, adjusted for age and sex were: absence of a partner (HR: 13,09; 95% CI: 4,04-42,31), obesity (HR: 2,89; 95% CI %: 1,59-5,27), peripheral arterial disease (HR: 2,26; CI 95%: 1,25-4,09), years of evolution of diabetes mellitus ≥ 15 years (HR: 1,99; CI 95 %: 1,04-3,82). In turn, for cardiovascular mortality were: obesity (HR: 6,42; 95% CI: 2,07-19,87), peripheral arterial disease (HR: 3,88; 95% CI: 1,39-10,79) and heart disease (HR: 4,11; 95% CI: 1,62-10,46). Conclusions: Evolution of diabetes mellitus greater than or equal to 15 years, not having a partner, obesity and peripheral arterial disease were associated with all-cause mortality. Regarding death from cardiovascular disease, the associated variables were obesity, peripheral arterial disease, and heart disease.